TRAINING OF HEALTH CADRE IN KINDERGARTEN (TK) FAJAR RACHMA ON IMPROVING CHILDREN'S DENTAL AND ORAL HEALTH - Sunnah, Tahta Danifatis; Balqis, Iqraini ` (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: The School Dental Health Program (UKGS) is a dental health improvement program that starts an early age in children. The program began to be held at the basic education level at the elementary, kindergarten and PAUD levels. The UKGS program is focused on pre-school age children (TK), this is a special consideration because pre-school age children are still not able to independently understand the importance of maintaining dental and oral health with certain techniques. The purpose of this program was to form dental and oral health cadres in the educational environment of Fajar Rachma Kindergarten and to improve the dental health of pre-school age childrenMethod: The training method used was in the form of playing educational videos about the growth and development of children's teeth and how to treat them. In addition, there will be interactive question and answer (discussion) to further open the horizons of kindergarten Result: Training activities for Kindergarten teachers went smoothly. Participants who attended this activity were Fajar Rachma Kindergarten Teachers totaling 8 people and Fajar Rachma Kindergarten children totaling 82 childrenConclusion: The training activities were very useful for the teachers and children of Fajar Rachma Kindergarten. The teachers already have knowledge and educational tools for children's dental health so that Fajar Rachma Kindergarten teachers can carry.